Laceration Repair for Emergency Physicians - Alisa Wray; Shannon Toohey (eScholarship Publishing, University of California, 2017)
Audience: This TBL is appropriate for medical students and all levels of residents. Introduction: Lacerations are one of the most common chief complaints presenting to the emergency department, representing 8.2% of ED visits.1 Wound management is one of the emergency medicine milestones.2 As such, it is an essential skill to cover when training emergency physicians. Historically, training programs correlate competency with quantity of procedures, with little focus on the quality.3 Objectives: By the end of this educational session, the learner will: 1) List the appropriate types and sizes of suture for various locations and types of lacerations. 2) Understand various suturing techniques and their indications, and 3) Show proficiency in performing various suturing techniques including: simple interrupted, horizontal mattress, vertical mattress, and repair of V-shaped lacerations. Method: This is an mTBL (modified team based learning) session.